Implementasi Teknologi Pengendalian Hayati Hama Kelapa Thosea monoloncha Meyrick dengan Nuclear Polyhedrosis Virus (NPV) [Biological Control Technology Implementation on Coconut Pest Thosea monoloncha Meyrick Using Nuclear Polyhedrosis Virus (NPV)] - Fredy Lala; Andriko Noto Susanto; Meldy L.A Hosang; Deciyanto S (Buletin Palma, 2018)
The nettle caterpillars pest Thosea monoloncha (Limacodidae: Lepidoptera) has attacked the coconut plant in Tolonuo Island, North Halmahera district, North Maluku Province with the intensity of attacked varied from light  minor damage to severe damage. This research purpose is to control the population of nettle caterpillars T. monoloncha and the response of farmers to technology using Nucleo Polyhedrosis Virus (NPV). The study was conducted from December 2014 to November 2015. The stages of this study are consisted of (a) observation of pest population T. monoloncha, (b) determination of plant damage intensity and (c) farmerd response to control technology. The results showed that the application of NPV extract can decrease the population of coconut pest T. monoloncha, the intensity of the damage decrease from severe, heavy and moderate to light damage. In additon, it also increase the amount of frond and coconut production from 14 to 45 nuts per tree. Farmers' response to various aspects of technology varied from 63.5-97.5%. ABSTRAKHama ulat api Thosea monoloncha (Limacodidae: Lepidoptera) telah menyerang tanaman kelapa di Pulau Tolonuo, Kabupaten Halmahera Utara, Provinsi Maluku Utara dengan intensitas kerusakan bervariasi dari ringan sampai sangat berat. Penelitian bertujuan untuk mengendalikan populasi hama ulat api T. monoloncha dan respon petani terhadap teknologi pemanfaatan Nucleo Polyhedrosis Virus (NPV). Penelitian dilaksanakan pada bulan Desember 2014 sampai November 2015. Hasil penelitian menunjukkan bahwa aplikasi ekstrak NPV dapat menurunkan populasi hama kelapa T. monoloncha, menurunkan intesitas kerusakan dari kerusakan sangat berat, berat dan sedang menjadi kerusakan ringan, meningkatkan jumlah pelepah dan buah kelapa dari 14 butir menjadi 45 butir per pohon. Respon petani terhadap berbagai aspek teknologi berada pada kisaran 63,5-97,5%.